2016
DOI: 10.1089/met.2015.0078
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of sRAGE Are Associated with Body Measurements, but Not Glycemic Parameters in Patients with Prediabetes

Abstract: In contrast to glycemic parameters, serum levels of sRAGE were negatively correlated with body measurements indicative of obesity in the prediabetic state. In addition, the negative correlation with LDL cholesterol levels suggests that sRAGE has a more robust association with metabolic syndrome than with prediabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 54 publications
2
7
0
2
Order By: Relevance
“…Our primary finding was that lean, NGT individuals possessed the greatest concentration of sRAGE isoforms compared with states of obesity, IGT, T2DM, or both. These findings are in accord with previous reports of lower sRAGE with obesity (5,13,18) and impaired glucose tolerance (3, 12, 22, 46). Importantly, we also demonstrate for the first time that reduced circulating concentrations of sRAGE isoforms are associated with greater proportional odds for the development of T2DM.…”
Section: Discussionsupporting
confidence: 93%
“…Our primary finding was that lean, NGT individuals possessed the greatest concentration of sRAGE isoforms compared with states of obesity, IGT, T2DM, or both. These findings are in accord with previous reports of lower sRAGE with obesity (5,13,18) and impaired glucose tolerance (3, 12, 22, 46). Importantly, we also demonstrate for the first time that reduced circulating concentrations of sRAGE isoforms are associated with greater proportional odds for the development of T2DM.…”
Section: Discussionsupporting
confidence: 93%
“…We found a strong inverse association between liver fat and sRAGE, but this association was largely dependent on BMI. Several studies have shown that obesity is a strong determinant of sRAGE levels explaining why the association is no longer present after adjustment for this confounder [32, 33]. In accordance with our data, Palma-Duran et al reported a decrease of sRAGE in NAFLD patients [27].…”
Section: Discussionsupporting
confidence: 91%
“…Specifically among those with diabetes, sRAGE studies have generally shown a positive association with risk of cardiovascular disease (7, 8, 12), mortality (1213), and renal outcomes (13). However, among community-based populations, sRAGE has been reported to be inversely associated with diabetes (14), body mass index (BMI), LDL-cholesterol (15), inflammation (16), cardiovascular events (1720), and chronic kidney disease (CKD) (21). esRAGE has been studied less, although higher levels have been associated with an increased risk of major adverse cardiovascular events in people with diabetes (22).…”
mentioning
confidence: 99%